2020
DOI: 10.1017/s1478951520000966
|View full text |Cite
|
Sign up to set email alerts
|

Church leaders and parishioners speak out about the role of the church in advance care planning and end-of-life care

Abstract: Objective Despite the increased focus on improving advance care planning (ACP) in African Americans through community partnerships, little published research focused on the role of the African American church in this effort. This study examines parishioner perceptions and beliefs about the role of the church in ACP and end-of-life care (EOLC). Method Qualitative interviews were completed with 25 church members (parishioners n = 15, church leader n = 10). The coding of data entailed a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In an article published in October 2020, Hendricks Sloan et al conducted interviews with AA church members and leaders and identified 7 themes, among them the need for health literacy in EOL care, involvement of church ministries to sustain ACP and EOL care programs, and lay health training on ACP and EOL care. 34 These themes intersect with the theme of support and partnerships identified in this review, and the study overall supports the promotion of ACP or EOL care literacy outreach in AA faith communities. In addition, a study from August 2020 by Johnson et al supports the data in this review, finding that beliefs and attitudes about hospice and palliative care changed after an educational intervention in AA churches.…”
Section: Discussionsupporting
confidence: 55%
“…In an article published in October 2020, Hendricks Sloan et al conducted interviews with AA church members and leaders and identified 7 themes, among them the need for health literacy in EOL care, involvement of church ministries to sustain ACP and EOL care programs, and lay health training on ACP and EOL care. 34 These themes intersect with the theme of support and partnerships identified in this review, and the study overall supports the promotion of ACP or EOL care literacy outreach in AA faith communities. In addition, a study from August 2020 by Johnson et al supports the data in this review, finding that beliefs and attitudes about hospice and palliative care changed after an educational intervention in AA churches.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, church-based models have been described as effective in community-led ACP education initiatives. 9 , 22 25 A notable example of a successful community-based initiative partnered with churches to train African American ‘lay health workers’. 9 , 25 Exploring a broader range of organizations to implement community-led ACP initiatives and investigating any differences in implementation experiences between organization types would be worthwhile future research.…”
Section: Discussionmentioning
confidence: 99%
“…Epps and colleagues12 describe the church as a key public health partner. Predominantly African American churches have untapped resources—parishioners, parish nurses, and existing health ministries—who are willing to receive training on ACP and EOL care services to increase knowledge on these issues within their church 13. State law and policy now support the training of qualified people to facilitate ACP in several states such as Virginia14–16 and to recognize a broader range of strategies to record ACP wishes 17.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Predominantly African American churches have untapped resourcesparishioners, parish nurses, and existing health ministries-who are willing to receive training on ACP and EOL care services to increase knowledge on these issues within their church. 13 State law and policy now support the training of qualified people to facilitate ACP in several states such as Virginia [14][15][16] and to recognize a broader range of strategies to record ACP wishes. 17 As liaisons to churches, health care providers such as nurses, physicians, social workers, pharmacists, and specially trained lay ACP facilitators can provide partnership in unique coalitions among the community and health system, facilitating education and training on ACP.…”
mentioning
confidence: 99%